GAP implementasi HAM dalam regulasi keperdataan Islam di Indonesia: Keterlantaran anak - Islamiyah, Lia Novita Cahya (Maliki Interdisciplinary Journal, 2024)
Human Rights (HAM) are fundamental principles guarantee that every individual has the right to life, freedom and prosperity. In Indonesia, with the largest Muslim population in the world, Islamic civil regulations play an important role in regulating personal and family life. However, the application of human rights in Islamic civil regulations is often a complex and controversial issue, especially when related to the protection of neglected children. Abandoned children are a very vulnerable group and require special protection from the state and society. This research aims to examine in depth the gap in the implementation of human rights in Islamic civil regulations in Indonesia, especially in the context of child neglect. Apart from that, this research also aims to explore the relevance between human rights and Islamic sharia and identify the legal basis and arguments underlying child protection in Islam and Indonesian law. It is hoped that this research will provide comprehensive insight and based recommendations to strengthen the protection of neglected children in Indonesia. This research uses a literature study or literature review method to explore the topics discussed. This research reveals that there are significant gaps in the implementation of human rights in Islamic civil regulations in Indonesia. This gap can be seen in various aspects, especially in terms of child adoption. The concept of adoption in Islamic law (tabanni) is different from the concept of adoption in Indonesian national law which grants certain rights to adopted children. In Islam, adopted children are not considered biological children and do not have the same inheritance rights, which creates gaps in legal protection for adopted children.